ARTICLES REVIEW: Ethno-Pharmaceutical Study of Medicinal Plants for Care and Treatment of Wounds in Indonesia: Systematic Data Search and Preclinical Review - Kusumo, Djati Wulan; Erlita Layina Sulistiyowati; Habibatur Rohmah; Nailus Amany Melinda (Tropical Biopharmaca Research Center, IPB University, 2023)
Ethnopharmacy study is an approach used to explore local knowledge of a particular community in the use of medicinal plants. This article discusses treatment methods and medicinal plants used for the treatment and care of wounds in several regions in Indonesia. In addition, this study is also useful to find out drugs from natural ingredients related to their bioactivity. The method used is literature study, while the data used are articles, databases and textbooks published from 2011-2021. Literature information searches are carried out using electronic search engines for articles and research journals published on several sites, such as Google, Pubmed, NCBI, Elsevier, and others. The results of the data obtained concluded that there were 27 types of plant species that were used traditionally and 15 who have already undergone preclinical testing for wound treatment and care.